Osteosarcoma in Pediatric Patients and Young Adults: A Single Institution Retrospective Review of Presentation, Therapy, and Outcome. (30th April 2014) - Haddox, Candace L.; Han, Gang; Anijar, Leon; Binitie, Odion; Letson, G. Douglas; Bui, Marilyn M.; Reed, Damon R.
Abstract : Background . Little is known about how cumulative chemotherapy delivery influences the poorer outcome observed in young adult (YA, 18–40 years) versus pediatric (<18 years) osteosarcoma patients. Here, we retrospectively examined differences in presentation, therapy, including cumulative chemotherapy dose, and outcome in YA and pediatric patients. Methods . We reviewed 111 cases of high-grade osteosarcoma at Moffitt Cancer Center between 1988 and 2012. Presentation factors, therapies, and survival were compared between YA and pediatric cohorts. Results . The cohorts were equivalent with respect to metastatic status, gender, tumor size, tumor site, and histological subtype. We found that the YA patients tended to have poorer histologic response to neoadjuvant chemotherapy measured by necrosis with 55% and 35% of pediatric versus YA patients responding favorably (P = 0.06 ). Only 39% of YA patients achieved the typical pediatric dose of methotrexate, doxorubicin, and cisplatin. These patients had a 3-year EFS of 76% (CI 53–100%) versus 47% (CI 26–69%;P = 0.09 ) in those who received less chemotherapy. Conclusion . Age continues to be a prognostic factor in osteosarcoma. Our study suggests that presentation factors are not associated with prognosis, while poorer response to chemotherapy and lower cumulative dose of chemotherapy delivered to YA patients may contribute to poorer outcomes.